Oxygen defect modified ferroelectric compound Z-type heterojunction photocatalytic material and preparation method and application thereof

By modifying ferroelectric compounds in the oxygen defect state, Bi2WO6-x/g-C3N4 composite material was prepared, and Z-type heterojunction was constructed, which solved the problems of the bandwidth of the band gap width of the existing ferroelectric photocatalytic materials and the easy recombination of photogenerated electron holes, and realized that The effect of efficient degradation of pollutants under visible light is achieved.

CN116174002BActive Publication Date: 2025-02-18SHANGHAI RES INST OF MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211569340.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-08
Publication Date
2025-02-18
Estimated Expiration
2042-12-08

AI Technical Summary

Technical Problem

The band gap width of existing ferroelectric photocatalytic materials is wide, and photogenerated electron holes are easy to recombine, resulting in low visible light utilization efficiency.

Method used

By introducing oxygen defective state modified ferroelectric compounds, Bi2WO6-x/g-C3N4 composite materials were prepared by hydrothermal solvent-thermal method and metal reduction heat method, Z-type heterojunction was constructed, widening the visible light absorption range and improving photoelectric conversion efficiency.

Benefits of technology

It realizes efficient degradation of pollutants under visible light, improves the photocatalytic activity of the catalyst and the visible light response range, and enhances the separation ability of electron holes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116174002B_ABST
    Figure CN116174002B_ABST
Patent Text Reader

Abstract

The present invention relates to an oxygen defect-modified ferroelectric compound Z-type heterojunction photocatalytic material and a preparation method and application thereof, and belongs to the field of photocatalytic technology. The present invention utilizes bismuth tungstate and carbon nitride to construct a heterojunction while introducing an oxygen defect state, thereby forming an amorphous layer with a large number of electron donor states concentrated at the heterojunction interface to stabilize the formation of the heterojunction. The introduction of oxygen vacancies, on the one hand, introduces donor energy levels inside the ferroelectric material to enhance the utilization efficiency of visible light, and on the other hand, the oxygen vacancy amorphous layer formed on the surface of the ferroelectric material nanoparticles is more conducive to the charge transfer between the heterojunctions, thereby stabilizing the structure of the Z-type heterojunction, thereby achieving the visible light catalytic efficient degradation of pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of photocatalysis, and in particular relates to an oxygen defect-modified ferroelectric compound Z-type heterojunction photocatalytic material, and a preparation method and application thereof. Background Art

[0002] With the development of society, environmental pollution has become a global problem and has received more and more attention. As an advanced oxidation method, semiconductor photocatalysis technology can use ultraviolet light or visible light to form various reactive oxygen species (ROS) for redox degradation of organic pollutants. It is considered to be an ideal "green" technology to solve environmental pollution.

[0003] Photocatalysts, as the core of photocatalytic technology, are the key to achieving efficient photocatalytic degradation of organic matter. However, traditional metal oxide semiconductors, such as TiO2 and ZnO, have disadvantages such as low photoconversion efficiency and easy recombination of carriers. Ferroelectric semiconductors can effectively reduce the recombination rate of electrons and holes due to the intrinsic built-in electric field established by their internal spontaneous polarization. At the same time, the larger photovoltaic voltage of ferroelectric materials can also effectively enhance the photoelectric conversion efficiency. As a kind of dielectric material, ferroelectric materials face the problem of large bandgap width (>2.7eV), which leads to the traditional ferroelectric materials headed by bismuth tungstate (Bi2WO6) can only use ultraviolet light as the energy source for electron excitation. In order to improve the utilization efficiency of the full band of solar energy, the introduction of shallow donor energy levels in the bandgap of ferroelectric materials, reducing the energy barrier of electron transition, expanding its light absorption range and inhibiting the separation of photogenerated charges have become the main research and development directions.

[0004] There are two commonly used strategies to adjust the band gap by introducing impurity energy levels: one is to introduce multi-electron elements into the matrix solid solution to form ion substitution, but in traditional oxides this method may change the structure and properties of the main compound; another effective method to adjust the band gap width is to introduce oxygen vacancies (OV) in situ to form a large number of electron donors, which appear as shallow donor energy levels in the energy band, thereby enhancing the ferroelectric material's absorption of solar energy in the visible and infrared bands. At the same time, by constructing a heterojunction, the photoelectric conversion efficiency can be better improved and the separation of carriers can be enhanced. At present, it is widely recognized that the heterojunction technology that can achieve effective interface transfer and spatial separation of electrons and holes under photoexcitation conditions is mainly the Z-type heterojunction. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of wide bandgap, easy recombination of photogenerated electrons and holes, low visible light utilization efficiency, etc. of the ferroelectric photocatalytic materials synthesized in the prior art, and to provide an oxygen defect-modified ferroelectric compound heterojunction photocatalytic material and its preparation method and application.

[0006] The present invention successfully prepared oxygen-deficient bismuth tungstate and graphite phase carbon nitride (Bi2WO) by hydrothermal solvent thermal method and metal reduction thermal method. 6-x / g-C3N4) composite materials can be used to efficiently degrade pollutants under visible light.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] The present invention provides an oxygen-deficient state modified ferroelectric compound heterojunction photocatalytic material, which is Bi2WO composed of oxygen-deficient state bismuth tungstate and graphite phase carbon nitride. 6-x / g-C3N4 composite Z-type heterojunction photocatalytic material, graphite phase carbon nitride is represented by g-C3N4, oxygen defect state bismuth tungstate is represented by Bi2WO 6-x , where 0≤x<6,

[0009] g-C3N4 is used as a carrier. g-C3N4 has a two-dimensional nanosheet structure. Oxygen vacancies introduce oxygen-deficient bismuth tungstate as a photocatalytic active component. Bi2WO 6-x With rod-like nanostructure, Bi2WO 6-x Evenly dispersed on the surface of the carrier, g-C3N4 and Bi2WO 6-x The mass ratio is 0.3:0.1~0.5.

[0010] Specifically, in the present invention, oxygen-deficient bismuth tungstate Bi2WO 6-x Specifically, Bi2WO6 nanoparticles coated with an oxygen-deficient bismuth tungstate amorphous layer, where the oxygen-deficient bismuth tungstate amorphous layer is represented by Bi2WO 6-x , where 0≤x<6.

[0011] The oxygen-deficient state modified ferroelectric compound heterojunction photocatalytic material provided by the present invention utilizes the amorphous layer formed by the concentrated oxygen vacancies on the surface of bismuth tungstate to induce the effective construction of the heterojunction structure. At the same time, the oxygen vacancies broaden the visible light absorption range of the ferroelectric material, thereby achieving the effect of visible light catalytic efficient degradation of pollutants.

[0012] The present invention also provides a method for preparing the oxygen defect modified ferroelectric compound heterojunction photocatalytic material, wherein Bi2WO 6-x Adding to g-C3N4, including the following steps:

[0013] Step 1, weigh Bi(NO3)3·5H2O and Na2WO4·2H2O, disperse them in ethylene glycol solution respectively and sonicate until they are dissolved into clear transparent solutions; then dissolve melamine in ethylene glycol and sonicate until dissolved; mix the three into a milky turbid solution and continue sonicating;

[0014] Step 2: transferring the solution obtained in step 1 to a polytetrafluoroethylene reactor for hydrothermal reaction;

[0015] Step 3: cross-wash the reaction product of step 2 with anhydrous ethanol and deionized water, filter, and then dry to obtain a powder;

[0016] Step 4: Place the powder obtained in step 3 in a vacuum tube furnace and calcine it in an argon atmosphere with low oxygen partial pressure to obtain an oxygen-deficient state modified ferroelectric compound heterojunction photocatalytic material, namely, Bi2WO composed of oxygen-deficient state bismuth tungstate and graphite phase carbon nitride. 6-x / g-C3N4 composite Z-type heterojunction photocatalytic material.

[0017] In some embodiments of the present invention, in step 1, the molar ratio of Bi element to W element is 2:1.

[0018] In some embodiments of the present invention, in step 1, the ultrasonication time is 0.5 to 1.5 h.

[0019] In some embodiments of the present invention, in step 1, the dissolution temperature of melamine in ethylene glycol is 50°C to 90°C, preferably 60°C to 80°C.

[0020] In some embodiments of the present invention, in step 2, the hydrothermal reaction conditions are: reacting at 180-200° C. for 12-24 hours.

[0021] In some embodiments of the present invention, in step three, the drying condition is: drying at 60-80° C. in a forced air drying oven.

[0022] In some embodiments of the present invention, in step 4, the calcination conditions are: maintaining a vacuum atmosphere of -0.1 MPa in an argon atmosphere, calcining at 500°C to 600°C, and the calcination time is 1 to 6 hours.

[0023] The present invention also provides a catalyst working electrode prepared based on the oxygen defect state modified ferroelectric compound heterojunction photocatalytic material.

[0024] Furthermore, the preparation method of the catalyst working electrode prepared based on the oxygen defect state modified ferroelectric compound heterojunction photocatalytic material is:

[0025] The ITO conductive glass was ultrasonicated with toluene, acetone, ethanol and deionized water for 30 minutes in sequence, 5 mg of oxygen defect-modified ferroelectric compound heterojunction photocatalytic material was weighed, 300 μL of isopropanol was added, and the mixture was ultrasonicated for 30 minutes to prepare a suspension; 150 μL of the above suspension was transferred with a pipette and evenly dropped on the ITO glass (the suspension was required to be evenly dispersed on the glass), and dried at room temperature to form a catalyst working electrode.

[0026] The present invention also provides the application of the oxygen defect state modified ferroelectric compound heterojunction photocatalytic material in efficiently degrading pollutants under visible light.

[0027] The present invention uses a method of introducing oxygen defect states while constructing a heterojunction by combining bismuth tungstate and carbon nitride, and forms an amorphous layer with a large number of electron donor states concentrated at the heterojunction interface to stabilize the formation of the heterojunction. The introduction of oxygen vacancies, on the one hand, introduces donor energy levels inside the ferroelectric material to enhance the utilization efficiency of visible light, and on the other hand, the oxygen vacancy amorphous layer formed on the surface of the ferroelectric material nanoparticles is more conducive to the charge transfer between the heterojunctions, thereby stabilizing the structure of the Z-type heterojunction, thereby achieving the effect of visible light catalytic efficient degradation of pollutants.

[0028] In some embodiments of the present invention, the oxygen defect state modified ferroelectric compound heterojunction photocatalytic material can be used in the photocatalytic degradation of methylene blue (MB). A feasible specific method is provided as follows: after the degradable material and the catalytic material are mixed, after reaching adsorption equilibrium under dark reaction conditions, a photocatalytic reaction is carried out to complete the degradation process, and the reaction liquid obtained in the degradation process is subjected to solid-liquid separation to obtain a degradation liquid and a used catalytic material; after filtering the degradation liquid through a filter membrane, the relative degradation content is determined in a UV-visible spectrophotometer.

[0029] In one embodiment, the degradation product is MB, the concentration of the degradation product is 10 ppm, the amount of the degradation product added is 100 mL, the amount of the catalytic material added is 10 mg, the simulated fluorescent lamp is a 500W xenon lamp, and the illumination wavelength is visible light (>420 nm).

[0030] The present invention also provides a recycling experiment of the oxygen defect modified ferroelectric compound heterojunction photocatalytic material, and the method steps are as follows: after the reaction is completed, the used catalytic materials obtained after solid-liquid separation are washed with ethanol, and then dried at 60-80°C for 6 hours to obtain the catalytic material for the next step of photocatalytic degradation cycle.

[0031] Compared with the prior art, the present invention has the following advantages:

[0032] 1. The present invention calcines Bi2WO6 nanoparticles in a low oxygen partial pressure atmosphere to generate an amorphous layer with concentrated oxygen vacancies on the surface of the nanoparticles, thereby causing energy level defects. By changing the chemical properties of Bi2WO6, narrowing the band gap and adjusting the electronic structure, the visible light response range of the catalyst is effectively improved, and the photocatalytic activity of the catalyst is enhanced.

[0033] 2. The construction of the two-dimensional planar structure of the g-C3N4 catalyst in the present invention can provide a large specific surface area and easy diffusion channels for photogenerated carriers, thereby improving light capture, accelerating the mass transfer process, and providing more active sites for photocatalytic reactions.

[0034] 3. Bi2WO of the present invention 6-x / g-C3N4 Z-type heterojunction catalyst uses g-C3N4 as support, Bi2WO 6-x As photocatalytic active components. g-C3N4 and Bi2WO 6-x The close contact and mutual synergy between the interfaces effectively construct a Z-type heterojunction, improve the effective separation of photogenerated electrons and holes, and enhance the redox ability of electrons and holes.

[0035] 4. The construction of Z-type heterojunction effectively solves the disadvantage of rapid recombination of photogenerated carriers in g-C3N4 itself, and plays an effective role in the degradation of MB.

[0036] 5. Bi2WO 6-x / g-C3N4 Z-type heterojunction catalyst can be used in the photocatalytic degradation of MB. Its application operation requirements are not high, the reaction conditions are mild, and it is environmentally friendly. After the degradation process is completed, the catalyst can be separated from the degradation liquid by centrifugation, and the circulation effect is good. The present invention provides a new way for green and efficient heterojunction catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Bi2WO 6-x ,g-C3N4 and Bi2WO 6-x / XRD of g-C3N4 composites;

[0038] Figure 2 Bi2WO 6-x TEM of / g-C3N4 composites;

[0039] Figure 3 Bi2WO 6-x / EDS spectrum of g-C3N4 composites;

[0040] Figure 4 Bi2WO 6-x Electron paramagnetic resonance (EPR) of materials;

[0041] Figure 5 Bi2WO 6-x ,g-C3N4 and Bi2WO 6-x Photogenerated current test diagram of / g-C3N4 composite material;

[0042] Figure 6 Bi2WO 6-x ,g-C3N4 and Bi2WO 6-x / AC impedance spectroscopy of g-C3N4 composites;

[0043] Figure 7 Bi2WO6-x / degradation kinetics of g-C3N4 composites;

[0044] Figure 8 It is a photocatalytic degradation cycle experiment diagram in the embodiment;

[0045] Fig. 9 To show the effect of adding different free radical scavengers on the photodegradation rate of MB in the examples;

[0046] Fig.10 The figure is an inference of the photocatalytic degradation mechanism of MB in the example. DETAILED DESCRIPTION

[0047] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0048] Example

[0049] This embodiment provides a method for preparing an oxygen-deficient state modified ferroelectric compound heterojunction photocatalytic material and its application.

[0050] The preparation method of the oxygen defect modified ferroelectric compound heterojunction photocatalytic material is as follows:

[0051] 1. Dissolve 5mmol Na2WO4·2H2O and 5mmol Bi(NO3)3·5H2O in 20mL ethylene glycol respectively, and dissolve into a clear transparent solution under ultrasound for 0.5h. Slowly mix the two and place them in a reactor for solvent thermal synthesis, keep them at 200℃ for 24 hours, cool them to room temperature, filter and dry them to obtain powder. Place the powder in a tube furnace with argon atmosphere, adjust the pressure to vacuum -0.1MPa, heat to 550℃ and calcine for 6h. After cooling, black bismuth tungstate monomer nanoparticles (Bi2WO4·2H2O) coated with oxygen defect shells are obtained. 6-x ).

[0052] 2. Mix 5g of melamine and 5g of thiourea and put them into a porcelain boat at 5℃·min. -1 The temperature was raised to 550°C and calcined for 4 h. After cooling, drying and grinding, g-C3N4 was obtained.

[0053] 3. Weigh Bi(NO3)3·5H2O and Na2WO4·2H2O in equal molar ratios, disperse them in ethylene glycol solution and sonicate for 0.5h until dissolved into a clear and transparent solution; then dissolve melamine in ethylene glycol and sonicate at 80°C until dissolved. Mix the three into a milky white turbid solution and continue sonicating. Transfer the resulting solution to a polytetrafluoroethylene reactor and react at 200°C for 24h; after the hydrothermal reaction is cooled to room temperature, filter and dry to obtain a powder. Place the powder in a vacuum tube furnace, maintain it in a vacuum atmosphere of -0.1MPa, and calcine it at 550°C for 6h. Obtain Bi2WO composed of bismuth tungstate nanoparticles coated with an oxygen-deficient amorphous layer and graphite phase carbon nitride. 6-x / g-C3N4 composite Z-type heterojunction photocatalytic material.

[0054] 4. ITO conductive glass is ultrasonicated with toluene, acetone, ethanol and deionized water for 30 minutes in sequence. Weigh 5 mg of electrode material, add 300 μL of isopropanol, mix and ultrasonicate for 30 minutes to make a suspension; use a pipette to transfer 150 μL of the above suspension, evenly drop it on the ITO glass (the suspension is required to be evenly dispersed on the glass), and dry it at room temperature to form a catalyst working electrode.

[0055] The three electrode materials are 5mg Bi2WO 6-x ,g-C3N4 and Bi2WO 6-x / g-C3N4 composite materials.

[0056] Figure 1 Bi2WO shown 6-x , g-C3N4 and Bi2WO 6-x / g-C3N4 composite material XRD diagram, as shown in the figure, through the X-ray powder diffraction experiment, it was observed that the composite material had relatively strong diffraction peaks at 2θ=28.32°, 32.28°, 47.16°, 55.96° and 58.60°, indicating that the composite material contained bismuth tungstate with diffraction data of ICSD: No.39-0256, and the two strong peaks of 13.2° and 26.9° corresponded to the (100) and (002) crystal planes of carbon nitride, respectively.

[0057] Figure 2 Bi2WO shown 6-x Transmission electron microscopy images of Bi2WO / g-C3N4 composite materials 6-x The nanorods and g-C3N4 nanosheets are stacked to form a heterojunction. 6-x The amorphous layer on the surface is clearly visible.

[0058] Figure 3 Bi2WO shown 6-x / EDS spectrum of the g-C3N4 composite material. From the information in the table, it can be judged that the atomic ratio of oxygen does not meet the stoichiometric ratio of the original Bi2WO6, so there are certain oxygen defects in the composite material.

[0059] Figure 4 Bi2WO shown 6-x The electron paramagnetic resonance (EPR) of the material showed an obvious EPR signal at g=2.003, further proving the existence of oxygen vacancies.

[0060] Figure 5 Bi2WO shown 6-x ,g-C3N4 and Bi2WO 6-x Photocurrent test diagram of / g-C3N4 composite material. Generally speaking, the stronger the instantaneous photocurrent intensity, the higher the separation rate of photogenerated electrons and photogenerated holes of the material. 6-x The instantaneous photocurrent intensity of the / g-C3N4 composite material is between 90 and 110 μA / cm 2 Finally, it stabilized at 50μA / cm 2 Nearby, the separation efficiency of photogenerated electrons and photogenerated holes is high.

[0061] Figure 6 Bi2WO shown 6-x ,g-C3N4 and Bi2WO 6-x Electrochemical impedance spectroscopy of Bi2WO / g-C3N4 composite material. In the high frequency region, the composite material does not show an obvious semicircular structure. The intersection of the curve and the X-axis is taken as the impedance of the composite material, which represents the electronic conductivity of the material. The higher the slope of the curve, the better the electronic conductivity. As shown in the figure, Bi2WO 6-x / g-C3N4 composite materials have good electron conduction ability and good separation effect of photogenerated electrons and photogenerated holes.

[0062] Figure 7 The Bi2WO prepared in this example is shown 6-x / g-C3N4 catalytic degradation of MB absorption at different wavelengths. It can be seen from the figure that Bi2WO 6-x The degradation rate of / g-C3N4 photocatalyst reached 99.4% after 30 minutes of illumination.

[0063] The cyclic degradation results are as follows Figure 8 As shown in the figure, the cyclic test shows that the degradation rate of BPA can also reach 90% after 4 cycles under the same conditions. The reduction in degradation rate is due to some losses during the washing and drying process after the photocatalytic reaction, and stirring will also remove a small amount of catalyst powder. However, after 3 cycles, the catalyst activity remains relatively stable, indicating that the synthesized Bi2WO 6-x / g-C3N4 has certain stability and recyclability.

[0064] Fig. 9 In order to investigate the effect of adding different free radical scavengers on the MB photodegradation rate in the examples, different quenchers were added to the photocatalytic reaction system to detect the role of active substances in photocatalysis. Isopropyl alcohol (IPA) was selected as a scavenger of hydroxyl radicals (·OH), and p-benzoquinone (HQ) was selected as a scavenger of superoxide radicals (·O 2- ) scavenger, citric acid (CA) as a hole (h + ) scavenger. Fig. 9 As shown, to Bi2WO 6-x When HQ and CA were added to the photocatalyst reaction solution of / g-C3N4, the MB degradation efficiency was significantly reduced from 99.4% to 35% and 75%, respectively, indicating that 2- and h + After adding IPA, the photodegradation of MB decreased slightly, indicating that the effect of ·OH was negligible.

[0065] According to the above calculation results and free radical capture experiments, Bi2WO 6-x The photocatalytic mechanism of the / g-C3N4 composite material was investigated. The results are as follows Fig.10 First, it is speculated that Bi2WO 6-x The photoinduced carrier transfer between g-C3N4 and e-C3N4 follows the conventional type II charge separation pathway. - Migration of CB from g-C3N4 to Bi2WO 6-x CB,h + From Bi2WO 6-x VB migrates to VB of g-C3N4. 6-x For example, the CB potential (0.22 eV) is higher than that of O2 / ·O 2- (-0.33 eV) correction; therefore, Bi2WO 6-x e on CB - Cannot reduce O2 to O 2- At the same time, the VB potential of g-C3N4 (+1.32eV) is higher than that of OH - / ·OH (+1.99 eV) is more negative, indicating that the h on the g-C3N4 VB + No ·OH can be generated. This is inconsistent with the free radical capture experiment. Based on the above analysis, the migration path of photoinduced carriers cannot follow the traditional type II heterojunction. 6-x The existence of strong electrostatic attraction and band potential between them proposed a direct Z-scheme heterojunction migration path for photoinduced carrier separation. 6-xAfter the nanorods are electrostatically bonded, Bi2WO 6-x e on CB - Under the action of the built-in electric field, it quickly interacts with the h at the VB of g-C3N4 + The CB potential of g-C3N4 (-1.13 eV) is much higher than that of O2 / ·O 2- more negative, therefore, the e on g-C3N4 - It reacts with O2 adsorbed on the photocatalytic surface to generate O 2- Then, O2 decomposes into OH radicals. At the same time, Bi2WO 6-x The VB potential (2.8 eV) is higher than that of OH - / ·OH(+1.99eV) correction, indicating that Bi2WO 6-x h on VB + Can generate ·OH. Bi2WO 6-x The Z-type heterojunction of / g-C3N4 can + Stay at Bi2WO 6-x In the corrected VB potential energy, e - Remain in the more negative CB potential of g-C3N4. Therefore, they have strong oxidation and reduction abilities and can effectively degrade MB. Therefore, the Z-type heterojunction can effectively promote the photoinduced carrier separation and enhance the photocatalytic effect.

[0066] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing an oxygen defect-modified ferroelectric compound heterojunction photocatalytic material, characterized in that: Bi2WO was synthesized by solvothermal method and low-pressure calcination 6-x Adding to g-C3N4, including the following steps: Step 1: Weigh Bi(NO3)3∙5H2O and Na2WO4∙2H2O, disperse them in ethylene glycol solution and sonicate them until they are dissolved into clear transparent solutions; then dissolve melamine in ethylene glycol and sonicate them until dissolved; mix the three into a milky turbid solution and continue sonicating; Step 2: transferring the solution obtained in step 1 to a polytetrafluoroethylene reactor for hydrothermal reaction; Step 3: cross-wash the reaction product of step 2 with anhydrous ethanol and deionized water, filter, and then dry to obtain a powder; Step 4: Place the powder obtained in step 3 in a vacuum tube furnace, maintain it in a vacuum atmosphere of -0.1 MPa, and calcine it at 500°C to 600°C for 1 to 6 hours to obtain an oxygen-deficient state modified ferroelectric compound heterojunction photocatalytic material, namely, Bi2WO composed of oxygen-deficient state bismuth tungstate and graphite phase carbon nitride. 6-x / g-C3N4 composite Z-type heterojunction photocatalytic material; In step 1, the dissolution temperature of melamine in ethylene glycol is 50°C to 90°C; in step 2, the hydrothermal reaction conditions are: reacting at 180°C to 200°C for 12 to 24 hours; In the obtained oxygen-deficient state modified ferroelectric compound heterojunction photocatalytic material, graphite phase carbon nitride is represented as g-C3N4, and oxygen-deficient state bismuth tungstate is represented as Bi2WO 6-x , where 0<x<6, The oxygen defect modified ferroelectric compound heterojunction photocatalytic material uses g-C3N4 as a carrier. g-C3N4 has a two-dimensional nanosheet structure. Oxygen vacancies introduce oxygen defect bismuth tungstate as a photocatalytic active component. Bi2WO 6-x With rod-like nanostructure, Bi2WO 6-x Evenly dispersed on the surface of the carrier, g-C3N4 and Bi2WO 6-x The mass ratio is 0.3:(0.1~0.5).

2. The method for preparing the oxygen defect modified ferroelectric compound heterojunction photocatalytic material according to claim 1, characterized in that: In step 1, the molar ratio of Bi element to W element is 1:

1.

3. The method for preparing the oxygen defect modified ferroelectric compound heterojunction photocatalytic material according to claim 1, characterized in that: In step 3, the drying condition is: drying in a forced air drying oven at 60-80°C.

4. An oxygen defect modified ferroelectric compound heterojunction photocatalytic material, characterized in that: The method is prepared by any one of claims 1 to 3.

5. A catalyst working electrode prepared based on the oxygen defect modified ferroelectric compound heterojunction photocatalytic material according to claim 4.

6. A method for preparing a catalyst working electrode based on the oxygen defect modified ferroelectric compound heterojunction photocatalytic material according to claim 4, characterized in that: The preparation method is: The ITO conductive glass is ultrasonicated with toluene, acetone, ethanol and deionized water in sequence, the oxygen defect state modified ferroelectric compound heterojunction photocatalytic material according to claim 4 is weighed, isopropanol is added, and the mixture is ultrasonicated to prepare a suspension; the suspension is transferred with a pipette, evenly dropped on the ITO conductive glass, and dried at room temperature to form a catalyst working electrode.

7. Use of the oxygen-deficient state modified ferroelectric compound heterojunction photocatalytic material according to claim 4 to degrade pollutants under visible light.

Citation Information

Patent Citations

  • Preparation method and application of visible-light responsive g-C3N4 / BiVO4 heterojunction material

    CN109092343A

  • Bi2WO6@TCNQ photocatalyst and preparation method and application thereof

    CN110201725A

  • Graphite type carbon nitride composite photocatalytic material containing oxygen vacancy bismuth tungstate / oxygen-enriched structure as well as preparation method and application of graphite type carbon nitride composite photocatalytic material

    CN111604083A